2020
DOI: 10.1029/2020ja028281
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Solar Wind Structures at Mercury's Orbit

Abstract: Mercury's environment is characterized by a high variability and strength of the solar forcing. Its magnetosphere is completely reconfigured even for small changes in the interplanetary magnetic field and the solar wind (SW) dynamic pressure. Different configurations are due to occurrence of different structures in the SW. Among them, high speed streams from coronal holes, magnetic clouds, and noncompressive density enhancement have been analyzed to better characterize the Hermean conditions, which might be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
5
10
0
1
Order By: Relevance
“…The onset of events 3 and 4 occurred during this period and in coincidence with IMF rotations. These conditions suggest that a non-compressive density enhancement reached SolO, indicating a possible small eruption from the Sun (Gosling et al 1977;Diego et al 2020). The passage of a SIR-like magnetic structure started on July 21 and coincides with the observed low-energy ion event (middle panel in Fig.…”
Section: Appendix A: Electron Anisotropiessupporting
confidence: 70%
“…The onset of events 3 and 4 occurred during this period and in coincidence with IMF rotations. These conditions suggest that a non-compressive density enhancement reached SolO, indicating a possible small eruption from the Sun (Gosling et al 1977;Diego et al 2020). The passage of a SIR-like magnetic structure started on July 21 and coincides with the observed low-energy ion event (middle panel in Fig.…”
Section: Appendix A: Electron Anisotropiessupporting
confidence: 70%
“…Such distribution of the data is consistent with the expectation of the Parker spiral model for the IMF (Parker 1958;Chang et al 2019). At a certain θ, the distribution of the data is approximately symmetric with respect to f, which is in agreement with the result in Diego et al (2020) that the distribution of B Z in MSO is approximately symmetric with respect to B Z = 0 if the IMF data amounts are large enough. Figure 5(B) shows the data coverage in the θ-f plane when the spacecraft is at Y MSO > 1 R M , and the distribution is similar to that in Figure 5(A).…”
Section: Occurrence Rate Of the Esmpssupporting
confidence: 89%
“…Based on the distribution of their durations, the magnetic peaks can be divided into two groups: durations < and >0.6 s. The histograms in each group approximately obey the log-normal distribution expressed by i.e., the median durations are 0.3 s and 2.7 s for the left and right groups, respectively. Diego et al (2020) reported that the average speed is ∼384 km s −1 and the ion temperature is in the range of 1.4 × 10 4 -1.1 × 10 6 K for the solar wind at Mercury's orbit based on observations of HELIOS 1 and HELIOS 2 missions. In addition, we find that the magnetic peaks with a duration of <0.6 s prefer to occur during the weak IMF strength (as shown in Figure 6).…”
Section: Magnetic Peaks Upstream Of Mercury's Bow Shockmentioning
confidence: 99%
See 1 more Smart Citation
“…sonda Messenger en 2008 muestran que la magnetosfera es dinámica, presentando variaciones en el flujo de partículas energéticas siendo posible ocurrencia de subtempestades [19,53,77,78].…”
Section: Magnetosferas De Planetas No Magnetizadosunclassified